Strategi Humas Dalam Meningkatkan Kualitas Pelayanan di RS Adi Husada Undaan Wetan Surabaya - Rahmi, Disty Auliya; Mamesah, Marline Merke; Haniwijaya, Silvia (Journal of Health Management Research, 2025)
Background: This research is motivated by the role of Public Relations in hospitals which is considered very important nowadays. This is driven by the public's tendency to use the internet more often to search for information about hospitals. Aims: This research aims to identify what strategies are carried out by Public Relations to improve the quality of service at Adi Husada Undaan Wetan Hospital Surabaya. Methods: This type of research uses a qualitative descriptive type. The data sources obtained by researchers used observation, interviews and documentation methods. Results: The results of the research show that the Public Relations strategy of the Adi Husada Undaan Wetan Surabaya Hospital is in accordance with the theory presented by the researcher, which includes strategies for publicity, persuasion, argumentation and image formation. This is done in several ways, such as providing attention and responding to customer complaints or complaints, frequently holding social service activities, optimally utilizing technology and social media to interact and communicate with external and internal parties. Adi Husada Hospital Undaan Wetan Surabaya has made efforts to improve the overall quality of its services, both in terms of reliability, guarantee, physical appearance, empathy and responsiveness. This has been proven to provide satisfaction for patients/customers. Conclusion: The performance of a publicist in improving the quality of service at Adi Husada Undaan Wetan Hospital is greatly influenced by various supporting and inhibiting factors. Apart from that, good cooperation with mass media and legal consultants is also the key to success. By understanding these factors in depth, Public Relations can design effective strategies to achieve its goals.